Steel sheet with variable thickness with reduced risk of delayed fracture after press hardening and
By applying a specific metal coating on the steel plate and performing flexible rolling and heat treatment, the problem of delayed fracture risk in press-hardened steel parts is solved, achieving variable thickness and excellent mechanical properties of the parts.
Patent Information
- Application Number
- CN202380056406.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2023-08-01
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to reduce the risk of delayed fracture in press-hardened steel components while maintaining the variable thickness and mechanical strength of the components.
Steel plates coated with a specific metal coating are used and components with variable thickness are formed by flexible rolling and heat treatment. The coating contains elements such as zinc, silicon, magnesium, etc., which are made by hot dip galvanizing and heat-treated after rolling to form a completely austenite microstructure.
It effectively reduces the amount of hydrogen adsorption in steel components, reduces the risk of delayed fracture, while maintaining the variable thickness of the component and excellent resistance to delayed fracture.
Smart Images

Figure BDA0005257393160000021 
Figure BDA0005257393160000071
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing press-hardened steel components having variable thickness and with minimal risk of delayed fracture.The invention is particularly well suited for the manufacture of motor vehicles. Background Art
[0002] It is known that certain applications (especially in the automotive field) require metal structures to be further lightened and reinforced in the event of impact. For this purpose, steel sheets with improved mechanical properties are usually used, which are formed by austenitizing and subsequent press hardening.
[0003] After press hardening, the sensitivity to delayed cracking increases with mechanical strength, because high residual stresses tend to remain after deformation. Combined with atomic hydrogen that may be present in the steel sheet, these stresses tend to cause delayed cracking, meaning that cracking occurs some time after the deformation itself. Hydrogen can gradually accumulate by diffusing into lattice defects such as matrix / inclusion interfaces, twin boundaries and grain boundaries. In the latter defects, hydrogen may become harmful when it reaches a critical concentration after a certain time. The delay is caused by the residual stress distribution area and the kinetics of hydrogen diffusion, and the hydrogen diffusion coefficient at room temperature is low. In addition, hydrogen located at the grain boundaries weakens their cohesion and helps to delay the appearance of intergranular cracks.
[0004] Press hardening is considered to be critical for hydrogen adsorption, which increases sensitivity to delayed fracture. Adsorption may occur under the austenitizing heat treatment, which is a heating step before the press forming itself. The saturation of hydrogen in the steel actually depends on the metallurgical phase. In addition, at high temperatures, water in the furnace decomposes into hydrogen and oxygen at the surface of the steel sheet.
[0005] It is also known in the automotive field to design components with variable thickness, so that mechanical resistance is present only in the areas where it is needed, without adding weight where it is not necessary. Weight reduction in motor vehicles is mandatory for reasons of energy consumption and exhaust emissions.
[0006] Components with variable thickness are usually produced by continuous flexible rolling (a process in which the plate thickness obtained after rolling is variable in the rolling direction). This occurs in relation to the load already applied to the plate by the rollers during the rolling process, as described in patent EP1074317. Flexible rolling is characterized by the deliberate change of the roll gap during the rolling operation. The purpose of flexible rolling is to produce rolled plates with a load-optimized and weight-optimized cross-section. The thickness of such a steel plate with variable thickness is inherited from rolling. Here and below, the rolling ratio is defined by the following formula:
[0007]
[0008] A blank cut from a strip having a variable thickness is generally referred to as a custom rolled blank. A custom rolled blank has one portion rolled at a certain rolling ratio and at least another portion rolled at a different rolling ratio. Due to flexible rolling, one portion of the custom rolled blank has a thickness t1 and at least another portion has a different thickness t2. Typically, such a rolling ratio has a value of 1% to 60%.
[0009] The resulting component with variable thickness is known to adsorb more hydrogen during the austenitizing heat treatment than a standard component with uniform thickness.
[0010] Patent application EP3489386 discloses coated steel sheets which are subjected to particularly low hydrogen adsorption during the press hardening process and whose surface enables simple and good further processing. The proposed solution is a coated steel substrate for hot working, comprising: a first coating comprising at least 85 wt. % of aluminum and a second coating covering the first coating; wherein the second coating is a copper-containing coating. The method according to this application is particularly suitable for flexible rolled strip materials, since after application of the nanocrystalline zinc-copper coating, the thinner rolled substrate parts also have an increased resistance to hydrogen adsorption. However, this solution requires a second coating on top of the aluminum-based coating. This results in additional process steps and corresponding costs and complexity.
[0011] Regarding hydrogen uptake during the heating step, not only the rolling ratio increases the amount of hydrogen, but also the parameters used to heat the blank. The higher the residence time or dew point in the furnace, the higher the amount of hydrogen in the press-hardened part will be. Summary of the invention
[0012] The object of the present invention is therefore to provide a steel sheet with variable thickness suitable for press hardening, which can be used to manufacture parts with variable thickness with limited hydrogen absorption independent of the heating time for press hardening. It is particularly intended to make it possible to obtain parts with excellent delayed fracture resistance.
[0013] This object is achieved by the steel sheets according to claims 1 to 3 .
[0014] Another object of the present invention is to provide a manufacturing method according to claim 4.
[0015] The objects of the invention are also achieved by providing a component according to claims 5 to 9 .
[0016] A final object of the invention is the use of such a component according to claim 10 . DETAILED DESCRIPTION
[0017] The present invention relates to a steel sheet coated with a metal coating, the metal coating comprising: zinc; silicon; magnesium; up to 3.0% iron; optionally an element selected from Pb, Ni, Zr, Hf, Sr, Sb, Pb, Ti, Ca, Mn, Sn, La, Ce, Cr, or Bi, the content of each element by weight being less than 0.3%; optionally up to 100 ppm calcium; and up to 0.02% unavoidable impurities, the balance being aluminum.
[0018] Preferably, the coating contains by weight 1.0 to 11.0% zinc, 1.0% to 7.0% silicon, 1.0% to 8.0% magnesium, up to 3.0% iron, and up to 0.02% unavoidable impurities, the balance being aluminum.
[0019] Advantageously, the coating comprises by weight 6.0% to 10.0% zinc, 1.0% to 4.0% silicon, 1.0% to 4.0% magnesium, up to 3.0% iron, and up to 0.01% unavoidable impurities, the balance being aluminum.
[0020] In another embodiment, the coating comprises, by weight percentage, 7.5% to 9.0% zinc, 2.0% to 4.0% silicon, and 1.5% to 2.5% magnesium, with the balance being aluminum.
[0021] The steel sheet according to the present invention can be manufactured by hot-dip galvanizing in a bath, the temperature of which is set to 600°C to 700°C, preferably 620°C to 650°C.
[0022] The coating weight controlled by the wiping process can be 50g / m for both sides of the steel plate combined 2 Up to 500g / m 2 , can be 80g / m 2 Up to 150g / m 2 , and preferably 100g / m 2 Up to 120g / m 2 .
[0023] Before being coated, the steel sheet according to the invention can be obtained by hot rolling and optionally cold rolling according to the desired thickness, which can be, for example, 1.0 mm to 4.0 mm.
[0024] The substrate to be coated may have any composition, depending on the desired mechanical properties. When steel is used for press hardening, its composition is preferably as described below.
[0025] After being coated, the coated steel sheet is subjected to a flexible rolling operation, after which the sheet has a variable thickness in the rolling direction.
[0026] The flexible rolling is preferably a cold rolling operation. The rolling ratio is 1% to 60%, preferably 5% to 50%. The re-rolled material obtained is then a custom rolled steel plate. The custom rolled steel plate is then cut to obtain a custom rolled blank. The flexible rolling operation usually takes place in one stage on a single stand, reversing rolling mill. The thickness of the coating is then also reduced. After rolling, the thickness of the plate can be as low as 0.8 mm or even 0.6 mm.
[0027] The method according to the invention comprises the following steps:
[0028] A. Providing a coated steel sheet according to the present invention having a variable thickness,
[0029] B. Cutting the rolled steel plates to obtain customized rolled blanks,
[0030] C. heat treatment of the custom rolled blank to obtain a fully austenitic microstructure in the steel,
[0031] D. Transfer the customized rolled blank into the pressing tool,
[0032] E. Press hardening of custom rolled blanks to obtain components with variable thickness,
[0033] F. Cooling the part with variable thickness obtained in step E) to obtain a press-hardened part with variable thickness.
[0034] Any steel can be advantageously used within the framework of the invention in step A. However, in the case where a steel with high mechanical strength is required, for parts of the structure of a motor vehicle, a steel with a tensile resistance higher than 500 MPa, advantageously between 500 MPa and 2000 MPa, before or after heat treatment can be used. The weight composition of the steel plate is preferably as follows: 0.03% ≤ C ≤ 0.50%; 0.3% ≤ Mn ≤ 3.0%; 0.05% ≤ Si ≤ 0.8%; 0.015% ≤ Ti ≤ 0.2%; 0.005% ≤ Al ≤ 0.1%; 0% ≤ Cr ≤ 2.50%; 0% ≤ S ≤ 0.05%; 0% ≤ P ≤ 0.1%; 0% ≤ B ≤ 0.010%; 0% ≤ Ni ≤ 2.5%; 0% ≤ Mo ≤ 0.7%; 0% ≤ Nb ≤ 0.15%; 0% ≤ N ≤ 0.015%; 0% ≤ Cu ≤ 0.15%; 0% ≤ Ca ≤ 0.01%; 0% ≤ W ≤ 0.35%, and the remainder is iron and unavoidable impurities from the manufacture of steel.
[0035] For example, the steel plate is 22MnB5 with the following weight composition: 0.20%≤C≤0.25%; 0.15%≤Si≤0.35%; 1.10%≤Mn≤1.40%; 0%≤Cr≤0.30%; 0.020%≤Ti≤0.060%; 0.020%≤Al≤0.060%; 0.002%≤B≤0.004%, and the remainder is iron and unavoidable impurities from the manufacture of steel.
[0036] In another embodiment, the steel plate has the following weight composition: 0.24%≤C≤0.38%; 0.40%≤Mn≤3%; 0.10%≤Si≤0.70%; 0.015%≤Al≤0.070%; Cr≤2%; 0.25%≤Ni≤2%; 0.015%≤Ti≤0.10%; Nb≤0.060%; 0.0005%≤B≤0.0040%; the remainder being iron and unavoidable impurities resulting from the manufacture of steel.
[0037] Alternatively, the steel plate may have the following weight composition: 0.30% ≤ C ≤ 0.40%; 0.5% ≤ Mn ≤ 1.0%; 0.40% ≤ Si ≤ 0.80%; 0.1% ≤ Cr ≤ 0.4%; 0.1% ≤ Mo ≤ 0.5%; 0.01% ≤ Nb ≤ 0.1%; 0.01% ≤ Al ≤ 0.1%; 0.008% ≤ Ti ≤ 0.003%; 0.0005% ≤ B ≤ 0.003%; 0.0% ≤ P ≤ 0.02%; 0.0% ≤ Ca ≤ 0.001%; 0.0% ≤ S ≤ 0.004%; 0.0% ≤ N ≤ 0.005%, with the remainder being iron and unavoidable impurities resulting from the manufacture of the steel.
[0038] In another embodiment, the steel plate has the following weight composition: 0.040%≤C≤0.100%; 0.80%≤Mn≤2.00%; 0%≤Si≤0.30%; 0%≤S≤0.005%; 0%≤P≤0.030%; 0.010%≤Al≤0.070%; 0.015%≤Nb≤0.100%; 0.030%≤Ti≤0.080%; 0%≤N≤0.009%; 0%≤Cu≤0.100%; 0%≤Ni≤0.100%; 0%≤Cr≤0.100%; 0%≤Mo≤0.100%, the balance being iron and unavoidable impurities from the manufacture of steel.
[0039] In another embodiment, the steel plate has the following weight composition: 0.06%≤C≤0.1%, 1%≤Mn≤2%, Si≤0.5%, Al≤0.1%, 0.02%≤Cr≤0.1%, 0.02%≤Nb≤0.1%, 0.0003%≤B≤0.01%, N≤0.01%, S≤0.003%, P≤0.020%, less than 0.1% of Cu, Ni and Mo, and the remainder is iron and unavoidable impurities generated by the manufacture of steel.
[0040] In another embodiment, the steel plate has the following weight composition: 0.015%≤C≤0.25%; 0.5%≤Mn≤1.8%; 0.1%≤Si≤1.25%; 0.01%≤Al≤0.1%; 0.1%≤Cr≤1.0%; 0.01%≤Ti≤0.1%; 0%≤S≤0.01%; 0.001%≤B≤0.004%; 0%≤P≤0.020%; 0%≤N≤0.01%; the balance being iron and unavoidable impurities from the manufacture of steel.
[0041] Alternatively, the steel plate has the following weight composition: 0.2%≤C≤0.34%; 0.5%≤Mn≤1.24%; 0.5%≤Si≤2.0%; 0%≤S≤0.01%; 0%≤P≤0.020%; 0%≤N≤0.01%, the balance being iron and unavoidable impurities from the manufacture of steel.
[0042] In step C, the heat treatment of the blank is carried out at a temperature of 800°C to 970°C, preferably 840°C to 950°C. The blank is kept during a residence time of 1 minute to 15 minutes to have a completely austenitic structure. During the heat treatment, the pre-coating layer forms an alloy layer with high corrosion resistance and wear resistance. The atmosphere of the furnace has an influence on the amount of hydrogen adsorbed into the steel sheet during the heat treatment. For example, in the case of a dew point of 20°C, it is known that hydrogen adsorption may be significant, while the risk of heat treatment in a dry atmosphere is much smaller.
[0043] In step D, after heat treatment, the blank is then transferred to a press-hardening tool.
[0044] In step E, press hardening is preferably carried out at a temperature of 600°C to 830°C.
[0045] In step F, the component is cooled in the press-hardening tool or after transfer to a special cooling tool. The cooling rate is controlled according to the steel composition in such a way that the final microstructure after press-hardening is consistent with the target mechanical properties. After press-hardening, the component can be additionally tempered to achieve the target microstructure and mechanical properties.
[0046] In a preferred embodiment, the steel microstructure comprises at least 95% martensite by volume.
[0047] In another embodiment, after press hardening, the steel microstructure comprises, by volume fraction, at least 50% martensite and less than 40% bainite.
[0048] In another embodiment, after press hardening, the steel microstructure comprises, by volume fraction, 5 to 20% martensite, up to 10% bainite, and at least 75% equiaxed ferrite.
[0049] The coated component according to the invention is thus obtained by press hardening, but can also be achieved by any suitable combination of cold stamping and press hardening.
[0050] The component obtained in step F is covered on its outer surface with a surface oxide layer. This oxide layer contains aluminum, zinc and magnesium from the coating and iron from the steel substrate. During the heat treatment, the iron diffuses through the coating.
[0051] A hydrogen content of 0.6 ppm or less is considered satisfactory after heat treatment in an atmosphere having a dew point of 20° C. In contrast, a hydrogen content of more than 0.6 ppm may cause a risk of delayed fracture later.
[0052] The inventors have found that the composition of the metallic coating has an influence on the hydrogen adsorption of the rolled material.The coating composition according to the invention allows the hydrogen content in the press-hardened component to be kept below 0.6 ppm, regardless of the rolling ratio.
[0053] It is believed that the surface oxide layer may act as a barrier to hydrogen, particularly if the oxide layer contains zinc, magnesium and if it has a minimum thickness.
[0054] The oxide layer contains elements from the coating. According to the invention, the oxide layer contains zinc and magnesium from the aluminum-based coating; and the minimum thickness of the oxide layer is 0.4 μm. Preferably, the minimum thickness of the oxide layer is 0.5 μm, advantageously 0.6 μm.
[0055] The invention will now be illustrated in experiments performed for reference only. The experiments are not limiting.
[0056] Example
[0057] For all samples, the steel sheet used was 22MnB5. The composition of the steel was as follows by weight: C = 0.22%; Mn = 1.2%; Si = 0.25%; Cr = 0.2%; Al = 0.041%; Ti = 0.04%; B = 0.003%.
[0058] All coatings were deposited by hot dipping in a single molten bath.
[0059] After coating deposition, some samples were kept unrolled and some other samples were rolled to 50%, ie their thickness became half of the thickness before rolling.
[0060] After the rolling step, the samples were heated in a furnace at 900°C with a dew point of +20°C for 5 minutes and 12 minutes.
[0061] After press hardening, two different measurements were performed: the amount of hydrogen and the thickness of the outer oxide layer.
[0062] The hydrogen content adsorbed by the steel sheet during the heat treatment was measured by thermal desorption using a thermal desorption analyzer or TDA. For this purpose, each sample was placed in a quartz chamber and slowly heated in an infrared furnace under a nitrogen flow. The released mixture hydrogen / nitrogen was picked up by a leak detector and the hydrogen concentration was measured by a mass spectrometer.
[0063] The oxide layer is measured by observing the cross section with a microscope. The minimum value along the cross section is reported.
[0064] The results are shown in Table 1:
[0065] Table 1:
[0066]
[0067] Underlined values Not according to the invention.
[0068] Tests 4 to 6, whose composition of the coating is not in accordance with the invention, contain more than 0.60 ppm of hydrogen, which causes a risk of delayed fracture. Their oxide layer thickness is too small. Tests 1 to 3 contain up to 0.40 ppm of hydrogen and thick oxide layers. They show that the problem of the risk of fracture is solved by a component coated with a coating in accordance with the invention having a variable thickness obtained by rolling one part thereof at a rolling ratio of 30% and another part thereof at a rolling ratio of 50%.
Claims
1. A coated steel sheet having a variable thickness in a rolling direction, having one portion rolled at a rolling ratio of 1% to 60% and at least another portion rolled at a different rolling ratio, wherein the coating comprises: zinc; silicon; magnesium; up to 3.0 wt. % iron; optionally an element selected from Ni, Zr, Hf, Sr, Sb, Pb, Ti, Ca, Mn, Sn, La, Ce, Cr, or Bi, the content of each of the optional elements by weight being less than 0.3 wt. %; optionally up to 100 ppm calcium; and up to 0.02 wt. % unavoidable impurities, the balance being aluminum, the coating having a coating weight of 50 g / m2 for the sum of both sides before flexible rolling. 2 Up to 500g / m 2 .
2. A coated steel sheet with variable thickness according to claim 1, wherein the coating comprises, by weight percentage, 1.0% to 11.0% zinc, 1.0% to 7.0% silicon, 1.0% to 8.0% magnesium, up to 3.0% iron, optionally up to 100 ppm calcium, and up to 0.02% unavoidable impurities, the balance being aluminum.
3. A coated steel sheet with variable thickness according to claim 2, wherein the coating comprises, by weight percentage, 6.0% to 10.0% zinc, 1.0% to 4.0% silicon, 1.0% to 4.0% magnesium, up to 3.0% iron, optionally up to 100 ppm calcium, and up to 0.01% unavoidable impurities, the balance being aluminum.
4. A pressing and hardening method comprising the following steps: A. Providing a coated steel sheet according to any one of claims 1 to 3, B. cutting the coated steel with variable thickness to obtain customized rolled blanks, C. heat treating said custom rolled blank to obtain a fully austenitic microstructure in said steel, D. transferring the customized rolled blank into a pressing tool, E. press hardening the tailor-made rolled blank to obtain a component with variable thickness, F. Cooling the part with variable thickness obtained in step E) to obtain a press-hardened part with variable thickness.
5. A press-hardened coated steel part with variable thickness obtained by press hardening a coated steel sheet with variable thickness according to any one of claims 1 to 3, and wherein the press-hardened part is covered with a surface oxide layer comprising aluminum, zinc and magnesium from the coating layer and iron from the steel substrate, the oxide layer comprising zinc oxide and magnesium oxide and having a minimum thickness of 0.40 μm, wherein the oxide layer thickness is measured by observing a cross section with a microscope. 6 . The press-hardened coated steel component having a variable thickness according to claim 5 , wherein a minimum thickness of the oxide layer is 0.50 μm, wherein the oxide layer thickness is measured by observing a cross section with a microscope.
7. The press-hardened coated steel component with variable thickness according to claim 5 or 6, wherein the microstructure of the press-hardened component comprises at least 95% martensite in volume fraction.
8. The press-hardened coated steel component with variable thickness according to claim 5 or 6, wherein the microstructure of the press-hardened component comprises at least 50% martensite and less than 40% bainite in volume fraction.
9. A press-hardened coated steel component with variable thickness according to claim 5 or 6, wherein the microstructure of the press-hardened component comprises 5% to 20% martensite, up to 10% bainite and at least 75% equiaxed ferrite.
10. Use of a component according to any one of claims 5 to 9 for the manufacture of a motor vehicle.
Citation Information
Patent Citations
Method for flexibly rolling a metal strip
EP1074317A2